Empowerment Programs and Social Construction of Poverty in the Lauje Indigenous Community, Parigi Moutong, Central Sulawesi - Krisdaryadi Ponco Nugroho; Muhammad Nur Ali; Zaiful Zaiful (Khazanah Sosial, 2024)
This study examines the phenomenon of poverty and the implementation of empowerment programs in the Lauje Indigenous Community in Parigi Moutong Regency, Central Sulawesi, with a particular focus on the social constructions that shape these programs. Employing a qualitative approach, data were collected through in-depth interviews, participatory observations, Focus Group Discussions (FGD), and document analysis. A total of 16 informants were purposively selected, including traditional leaders, women leaders, youth leaders, indigenous community members, government program field assistants, and village heads within the Lauje Indigenous Community. The findings reveal that poverty among the Lauje Indigenous Community is a multidimensional issue influenced by both structural and cultural factors. Structural factors include limited access to transportation, healthcare, education, and low market value for agricultural products. Cultural factors relate to local beliefs, such as having many children as a sign of good fortune and traditional parenting practices that restrict women’s roles in the household economy. Although the government has introduced empowerment programs under the Village SDGs framework, challenges persist due to limited infrastructure and low community participation. Existing empowerment initiatives have yet to significantly improve economic welfare, as they do not fully consider the socio-cultural conditions of indigenous communities. Meanwhile, the social construction of the Lauje Indigenous Community remains deeply rooted in values of mutual cooperation, solidarity, and harmony with nature. This social capital plays a crucial role in sustaining community life, yet it is gradually eroding due to modernization and materialism among younger generations. This study recommends that empowerment programs should be designed with greater sensitivity to local wisdom and actively involve indigenous communities in planning and execution. Furthermore, strengthening basic infrastructure, financial literacy, and entrepreneurship education is essential to enhancing the economic independence of the Lauje Indigenous Community. Lastly, efforts should be made to preserve social capital and traditional values, as they continue to serve as fundamental pillars of the community’s social and economic sustainability.